Phytoene Synthase: The Key Rate-Limiting Enzyme of Carotenoid Biosynthesis in Plants - Zhou, Xuesong; Rao, Sombir; Wrightstone, Emalee; Sun, Tianhu; Lui, Andy Cheuk Woon; Welsch, Ralf; Li, Li (Frontiers in Plant Science, 2022)
Phytoene synthase (PSY) catalyzes the first committed step in the carotenoid biosynthesis pathway and is a major rate-limiting enzyme of carotenogenesis. PSY is highly regulated by various regulators and factors to modulate carotenoid biosynthesis in response to diverse developmental and environmental cues. Because of its critical role in controlling the total amount of synthesized carotenoids, PSY has been extensively investigated and engineered in plant species. However, much remains to be learned on its multifaceted regulatory control and its catalytic efficiency for carotenoid enrichment in crops. Here, we present current knowledge on the basic biology, the functional evolution, the dynamic regulation, and the metabolic engineering of PSY. We also discuss the open questions and gaps to stimulate additional research on this most studied gene/enzyme in the carotenogenic pathway.